Absence of acidosis in the initial presentation of propionic acidaemia. Issue 3 (May 1995) - Walter, J. H.; Wraith, J. E.; Cleary, M. A.
Abstract : The clinical presentation and results of the initial biochemical and haematological investigations in 11 newborn term infants with propionic acidaemia are described. All patients had neurological symptoms. Only four had clinically important acidosis, but all had a raised blood ammonia. A diagnosis of propionic acidaemia should be considered in all newborn infants with unexplained neurological deterioration even in the absence of a metabolic acidosis.